Purinergic Signaling in Controlling Macrophage and T Cell Functions During Atherosclerosis Development - Ferrari, Davide; la Sala, Andrea; Milani, Daniela; Celeghini, Claudio; Casciano, Fabio (Frontiers in Immunology, 2021)
Atherosclerosis is a hardening and narrowing of arteries causing a reduction of blood flow. It is a leading cause of death in industrialized countries as it causes heart attacks, strokes, and peripheral vascular disease. Pathogenesis of the atherosclerotic lesion (atheroma) relies on the accumulation of cholesterol-containing low-density lipoproteins (LDL) and on changes of artery endothelium that becomes adhesive for monocytes and lymphocytes. Immunomediated inflammatory response stimulated by lipoprotein oxidation, cytokine secretion and release of pro-inflammatory mediators, worsens the pathological context by amplifying tissue damage to the arterial lining and increasing flow-limiting stenosis. Formation of thrombi upon rupture of the endothelium and the fibrous cup may also occur, triggering thrombosis often threatening the patient’s life. Purinergic signaling, i.e. cell responses induced by stimulation of P2 and P1 membrane receptors for the extracellular nucleotides (ATP, ADP, UTP and UDP) and nucleosides (adenosine), has been implicated in modulating the immunological response in atherosclerotic cardiovascular disease. In this review we will describe advancements in the understanding of purinergic modulation of the two main immune cells involved in atherogenesis, i.e. monocytes/macrophages and T lymphocytes, highlighting modulation of pro- and anti-atherosclerotic mediated responses of purinergic signaling in these cells and providing new insights to point out their potential clinical significance.